2016
DOI: 10.1636/j15-08.1
|View full text |Cite
|
Sign up to set email alerts
|

Losing legs and walking hard: effects of autotomy and different substrates in the locomotion of harvestmen in the genusPrionostemma

Abstract: Autotomy, the strategy of voluntarily releasing a leg during an encounter with a potential predator or in agonistic interactions between conspecifics, is common in animals. The potential costs of this behavior have been scarcely studied. In addition, locomotion and substrate-dependent performance might be affected by autotomy. We did a comparative and observational study to investigate whether losing legs affects the escape speed and trajectory of harvestmen in the genus Prionostemma Pocock, 1903 (Eupnoi: Scle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…This aligns with previous work on wolf spiders (Lycosidae) that found that autotomized spiders were slower following leg autotomy during horizontal running (Amaya et al, 2001;Apontes & Brown, 2005). Similar reductions in locomotor performance resulting from loss of a limb have been shown in stick insects (Carlburg, 1984), harvestman (Dominguez et al, 2016;Guffey, 1999;Houghton et al, 2011), decapod crustaceans (Juanes & Smith, 1995), and sea stars (Bingham, Burr, & Wounded Head, 2000). Additionally, Fleming and Bateman (2007) found that leg autotomy reduced endurance and increased the energetic cost of locomotion in field crickets (Gryllus bimaculatus).…”
Section: At Intermediate Nonvertical Inclines Burst Speeds Have Beensupporting
confidence: 85%
“…This aligns with previous work on wolf spiders (Lycosidae) that found that autotomized spiders were slower following leg autotomy during horizontal running (Amaya et al, 2001;Apontes & Brown, 2005). Similar reductions in locomotor performance resulting from loss of a limb have been shown in stick insects (Carlburg, 1984), harvestman (Dominguez et al, 2016;Guffey, 1999;Houghton et al, 2011), decapod crustaceans (Juanes & Smith, 1995), and sea stars (Bingham, Burr, & Wounded Head, 2000). Additionally, Fleming and Bateman (2007) found that leg autotomy reduced endurance and increased the energetic cost of locomotion in field crickets (Gryllus bimaculatus).…”
Section: At Intermediate Nonvertical Inclines Burst Speeds Have Beensupporting
confidence: 85%
“…Context‐ and substrate‐dependent effects of autotomy on locomotion have also been demonstrated. Examples include the width of the surface on which A. carolinensis could run (Hsieh, ), the degree of surface incline while moving in cellar spiders Pholcus manueli (Gerald et al, ) and fiddler crabs Uca pugilator (Gerald & Thiesen, ), as well as the three‐dimensional substrate complexity which affects movement in the harvestman taxa Leiobunum (Houghton, Townsend, & Proud, ), Holmbergiana weyemberghi (Escalante, Albín, & Aisenberg, ), and Prionostemma (Domínguez et al, ). Lastly, some studies have included the long‐term monitoring of animals post‐autotomy.…”
Section: Variation In the Costs And Benefits Of Autotomymentioning
confidence: 99%
“…They represent disturbed patches of vegetation cover with distinctive vegetation structure and a high proportion of bare ground (Davidson & Lightfoot, ; Case et al ., ; Lindtner et al ., ). Harvestman species exhibit substrate‐dependent trajectory patterns with greater speed on the soil than other substrates (Domínguez et al ., ). In contrast to spiders that are typical sit‐and‐wait predators (Riechert, ), harvestmen are rather active foragers (Chelini et al ., ; Schaus et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In other words, the strongest preference to the mounds showed long‐legged harvestmen, and on the other hand, short‐legged harvestmen showed no preference to mounds or grassland matrix. Harvestmen are active foragers and their locomotion skills are crucial for their survival (Chelini et al ., ; Schaus et al ., ; Domínguez et al ., ). The importance of leg length in harvestmen species for locomotion performance is well recognised (Pinto‐da‐Rocha et al ., ; Smith et al ., ).…”
Section: Discussionmentioning
confidence: 97%